Molecular characterization of Brucella ovis in Argentina - Alvarez, Lucía Paula (2020)
Brucellosis in rams is caused by Brucella ovis or Brucella melitensis and it is considered one of the most important infectious diseases of males in sheep-raising countries. Molecular characterization of Brucella spp. achieved by multi-locus variable number of tandem repeats analysis (MLVA) is a powerful tool to genotype Brucella spp. However, data regarding B. ovis genotyping is scarce. Thus, the aim of this study was to characterize the molecular diversity of B. ovis field-strains in Argentina. A total of 115 isolates of B. ovis from Argentina and Uruguay were genotyped using MLVA-16 and analyzed altogether with 14 publicly available B. ovis genotypes from Brazil. The Discriminatory Power (D) was 0.996 for MLVA-16 and 0.0998 for MLVA-8 and MLVA-11. Analysis of MLVA-16 revealed 100 different genotypes, all of them novel, including 90 unique ones. There was no correlation between geographical distribution and genotype and results showed a higher diversity within provinces than between provinces. Clustering analysis of the strains from Argentina, Uruguay and Brazil revealed that the 129 isolates were grouped into two clades. Whole Genome Sequencing analysis of the 19 B. ovis genomes available in public databases, and including some of the Argentinian strains used in this study, revealed clustering of the Argentinian isolates and closer relationship with B. ovis from New Zealand and Australia. This work adds new data to the poorly understood distribution map of genotypes regionally and worldwide for B. ovis and it constitutes the largest study of B. ovis molecular genotyping until now.